BIOGRAFI FRIEDRICH SILABAN PERANCANG ARSITEKTUR MASJID ISTIQLAL - Ojak Pasu P Simamora; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Friedrich Silaban is a famous Indonesian architect from Batak land precisely in Bonandolok district of North Tapanuli (now Humbang Hasundutan) North Sumatra. Friedrich Silaban is increasingly recognized in Indonesia after winning the construction contest Istiqlal Mosque. The purpose of this research is to know Friedrich Silaban and its role in the construction of the largest mosque in Indonesia, the Istiqlal Mosque. To find out the life of Friedrich Silaban, to find out the career path of Friedrich Silaban architect, to know how Friedrich Silaban won the Istiqlal Mosque contest, to know the obstacles faced by Friedrich Silaban in the construction of Istiqlal Mosque, to find out the Istiqlal Mosque Settlement by Friedrich Silaban and to know the old age Friedrich Silaban. The method used in this research is qualitative method. Data obtained from literature study results from various sources such as books, magazines, and internet media. The location of research from this thesis is in the city of Pekanbaru. This research has been conducted since the seminar exams The proposal is accepted until this thesis is completed. The results of this study found that Friedrich Silaban was born from the couple Jonas Silaban and Noria Simamora. Friedrich Silaban was born on December 16, 1912 and died on May 14, 1984. Friedrich Silaban was known as a Monumental Architect, because his architectural career career Friedrich Silaban handled many major projects and became a historic icon in Indonesia. And on July 5, 1955 the jury of Istiqlal Mosque construction established Friedrich Silaban as the first winner and performed at the Merdeka Palace, as well as conferring a gold medal weighing 75 grams and Rp. 25,000. Istiqlal Mosque was built on August 24, 1961 and inaugurated its use on February 22, 1978 by President Soeharto. The construction of the Istiqlal Mosque was financed from APBN of Rp.7,000,000.00 and US 12,000,000Keywords: Friedrich Silaban, Istiqlal Mosque, Bonandolok